PENGGUNAAN PESO MODEL DALAM PERANCANGAN STRATEGI ONLINE MARKETING UNTUK PROGRAM STUDI DESAIN KOMUNIKASI VISUAL - M. Lahandi Baskoro (Universitas Bunda Mulia, 2020)
There has been an increase in the number of universities providing Visual Communication Design (DKV) education in the past decade. The role of online marketing is increasingly significant in responding to competition between study programs because the target of their students is in the age range of 13 to 18 years Indonesian population who are already connected to the internet, which is 75.5% of the penetration rate. Meanwhile, the PESO model is a form of framework that can be used to facilitate designing online marketing strategies through utilization of various types of media. The purpose of this study is to: (1) explore how the PESO model can be used in designing online marketing strategies for visual communication design study programs; and (2) looking for examples of DKV study program promotions practices in each media based on the PESO model. As a result, the categorization of the PESO model makes it easy to design online marketing strategies based on its media characteristics and the examples found evidences that there are already DKV study programs conducting promotions in each media category based on the PESO model.